Pengaruh Variasi Defleksi Lateral Pada Baja Hollow Profil Persegi Terhadap Sifat Keausan, Kekerasan, Dan Struktur Mikro Hasil Proses Bending - Aprillio et al., Deary Nanda (Universitas Merdeka Malang, 2025)
ABSTRACT The bending process is a metal forming process where a metal will be bent with a bending machine and will form like the desired metal (curved). The bending process to make the product requires an external force (deflection). In this final project research there is a goal that is to be able to know the grain size on the specimen, the value of hardness after bending, the value of wear resistance after bending. In the manufacture of specimens using a square hollow steel profile with dimensions of 30 mm x 30 mm with a thickness of 1 mm. the specimen with the highest deflection got the highest hardness of 73.2 HRB resulting in smaller steel grains. At a deflection of 6mm it can be seen that the largest average grain size at the bottom is 0.635 mm2, at a deflection of 12 mm the largest grain size value is located at the bottom of 0.0449 mm2, and at a deflection of 18 mm the largest grain size is at the bottom. 0.0378 mm2. then the smallest hardness of 40.9 HRB causes the steel grains to get bigger. In the wear test, the harder the object being tested, the stronger the wear resistance.